Textiles in cultural relations between the Roman Empire and the Barbaricum (1st-3rd cent. AD) - Kaczmarek, Zofia (Studia Europaea Gnesnensia, 2015)
Textiles in cultural relations between the Roman Empire and the Barbaricum (1st-3rd cent. AD) - autoreferat rozprawy doktorskiej